Morphometric Characteristic of Glandular Stomach and Gizzard of the Common Scoter Melanitta nigra (Aves, Anseriformes) Wintering on the Polish Baltic Coast - Dziala-Szczepanczyk, E. (Вестник зоологии, 2007)
The material for studies were stomachs of 52 individuals of the Common Scoter Melanitta nigra obtained in winter in western parts of Polish Baltic coast. Six parameters of stomachs were established: glandular stomach weight (GSW) and length (GSL), gizzard length (GL) and width (GWi), combined length of both stomachs (GGL), and four measurements describing the birds’ body size: body weight (BW) and length (BL), sternum length (SL) and tarsus length (TL). Dimorphic differences connected with the birds’ sex and age in concerning average values of stomachs parameters and indices of their relative size were examined. Relationships among values of the stomach parameters and relationships between the values of the stomach parameters and the measurements describing the bird body size were analysed. Despite clearly marked sexual dimorphism in the bird body size in favour of males, only in three parameters GWi, GW, GGL, and in the index GGL/SL (both stomach length in relation to sternum length) drakes achieved significantly higher values than ducks. Adult and immature birds, both in the group of males and females, did not differ in body size and most average values of the stomach parameters. Only in the group of females adult individuals were characterised with heavier gizzard than immature individuals, and adult individuals of both sexes had wider gizzard than immature individuals. Except GSL and GSW, remaining parameters of the stomachs positively correlated with at least two body parameters of the birds. A positive correlation for the relation of GL to BL, TL, SL; GWi to BW, BL; GW to BW, BL; GGL to BW, TL, SL were shown. No relationship between GSL and gizzard measurements was noticed. But GSW was in a positive correlation with GWi and GW. Материалом для исследований послужили желудки 52 особей синьги Melanitta nigra, полученные зимой в западных районах польского побережья Балтики. Были определены 6 параметров желудков: масса (GSW) и длина (GSL) железистого желудка, масса (GW), длина (GL), ширина (GWi) мускульного желудкa и общая длина обоих желудков (GGL), а также 4 измерения, описывающие размеры тела птиц: масса (BW) и длина (BL) тела, длина грудины (SL) и длина цевки (TL). Исследовали диморфические различия, связанные с полом и возрастом птиц в объеме средних величин желудочных параметров и показателей их относительных размеров. Анализировали зависимости между величинами желудочных параметров и размерами тела птиц. Несмотря на четко обозначенный половой диморфизм по размерам тела птиц в пользу самцов, только по 3 параметрам GWi, GWL и GGL и по параметру GGL/SL (длины обоих желудков относительно длины грудины) селезни достигали действительно больших величин, чем утки. Птицы в возрасте adultus и immaturus как в группе самцов, так и самок не отличались размерами тела и в большинстве по средним величинам желудочных параметров. Только в группе самок взрослые особи характеризовались более тяжелым мускульным желудком, чем молодые, а взрослые особи обоих полов имели более широкий мускульный желудок, чем молодые. Кроме GSL и GSW остальные параметры желудков коррелировали положительно по крайней мере с двумя параметрами тела птиц. Определена положительная корреляция для связи GL c BL, TL и SL; GWi c BW и BL; GW c BW и BL; GGL c BW, TL и SL. Не обнаружена зависимость между GSL и измерениями мускульного желудка. Однако GSW находилась в положительной корреляции с GWi и GW.